Content expectations and dropout in Dutch vocational education - Irene Eegdeman (Empirical Research in Vocational Education and Training, 2020)
Abstract Unrealistic expectations with regard to one’s study program has been linked to negative consequences for future academic success. Previous studies that have shown this are often retrospective, however, and focus on performance-related expectations (e.g. expected grades), while unrealistic expectations about the required effort and the content of the program (content-related expectations) may be more relevant for explaining dropout in tertiary education. This study prospectively investigates whether the content-related expectations of 208 Dutch Sport Academy students elicited before the start of their vocational program are associated with subsequent dropout and academic performance. Our results show that dropped-out students did not differ in expected grades (even though they did differ in prevocational GPA). Moreover, their content-related expectations at the start of the program did not from successful students, nor were they any less realistic. Still, when retrospectively asked, 50% of the students answered that the concerning program did not fit. This suggests that retrospective reports of inadequate expectations may not reflect deficient expectations before starting the program. Instead, tertiary educational programs may defy expectations in both successful students and later unsuccessful students, with surprises being pleasant for successful students and unpleasant for unsuccessful ones.